Advancement in Biopolymer Assisted Cancer Theranostics - Bhattacharya, Tanima; Preetam, Subham; Ghosh, Basab; Chakrabarti, Tulika; Chakrabarti, Prasun; Samal, Shailesh Kumar; Thorat, Nanasaheb (ACS APPLIED BIO MATERIALS, 2023)
Applications of nanotechnology have increased the importance of research and nanocarriers, which have revolutionized the method of drug delivery to treat several diseases, including cancer, in the past few years. Cancer, one of the world’s fatal diseases, has drawn scientists’ attention for its multidrug resistance to various chemotherapeutic drugs. To minimize the side effects of chemotherapeutic agents on healthy cells and to develop technological advancement in drug delivery systems, scientists have developed an alternative approach to delivering chemotherapeutic drugs at the targeted site by integrating it inside the nanocarriers like synthetic polymers, nanotubes, micelles, dendrimers, magnetic nanoparticles, quantum dots (QDs), lipid nanoparticles, nano-biopolymeric substances, etc., which has shown promising results in both preclinical and clinical trials of cancer management. Besides that, nanocarriers, especially biopolymeric nanoparticles, have received much attention from researchers due to their cost-effectiveness, biodegradability, treatment efficacy, and ability to target drug delivery by crossing the blood–brain barrier. This review emphasizes the fabrication processes, the therapeutic and theragnostic applications, and the importance of different biopolymeric nanocarriers in targeting cancer both in vitro and in vivo, which conclude with the challenges and opportunities of future exploration using biopolymeric nanocarriers in onco-therapy with improved availability and reduced toxicity.